Rhizobium laguerreae Improves Productivity and Phenolic Compound Content of Lettuce (Lactuca sativa L.) under Saline Stress Conditions - Miguel Ayuso-Calles; Ignacio García-Estévez; Alejandro Jiménez-Gómez; José D. Flores-Félix; M. Teresa Escribano-Bailón; Raúl Rivas (Foods, 2020)
Lettuce (Lactuca sativa L.) is a widely consumed horticultural species. Its significance lies in a high polyphenolic compound content, including phenolic acids and flavonols. In this work, we have probed the ability of Rhizobium laguerreae HUTR05 to promote lettuce growth, under in vitro and greenhouse conditions (both non-saline and saline conditions). This strain has shown several in vitro plant growth promotion mechanisms, as well as capacity to colonize lettuce seedlings roots. We have analyzed the effect of the rhizobacterium inoculation on mineral and bioactive compounds in lettuce, under greenhouse conditions, and found a rise in the content of certain phenolic acids and flavonoids, such as derivatives of caffeoyl acid and quercetin. The genome analysis of the strain has shown the presence of genes related to plant growth-promoting rhizobacteria (PGPR) mechanisms, defense from saline stress, and phenolic compound metabolism (such as naringenin-chalcone synthase or phenylalanine aminotransferase).